Sex‐based difference in anticoagulated patients with mechanical prosthetic heart valves and long‐term mortality risk. Issue 5 (11th February 2021) - Pastori, Daniele; Poli, Daniela; Antonucci, Emilia; Menichelli, Danilo; Violi, Francesco; Palareti, Gualtiero; Pignatelli, Pasquale; ,
Abstract: Background: Vitamin K antagonists (VKAs) reduce thromboembolism in patients with mechanical prosthetic heart valves (MPHV). It is unclear whether a sex‐based difference in MPHV patients regarding valve site, anticoagulation quality, and mortality risk does exist. Methods: We analysed 2111 MPHV patients from the nationwide PLECTRUM study promoted by the Italian Federation of Anticoagulation Clinics (FCSA). We analysed the site of MPHV, anticoagulation quality, as assessed by the time in therapeutic range (TiTR), and mortality risk in women and men. Results: The mean age of the patients was 56.8 ± 12.3 years. Women were older with a lower prevalence of ischemic heart disease and smoking habit and a higher prevalence of atrial fibrillation at baseline. Aortic MPHV was more frequent in men (74.7% vs 43.3%, P  < .001), whereas mitral (41.1% vs 17.6%, P  < .001) and mitro‐aortic (15.6% vs 7.7%, P  < .001) MPVH in women. The association between female sex and mitral/mitro‐aortic site remained at multivariable logistic regression analysis (Odds Ratio 3.623, 95% Confidence Interval [CI] 2.947‐4.455, P  < .001). Regarding anticoagulation quality, women showed lower mean TiTR (63.0 ± 19.4 vs 57.5 ± 19.2, P  < .001), and a higher proportion of TiTR < 60% (54.9% vs 43.3%, P  < .001). During a mean follow‐up of 123 months (21 665 pt‐years), 152 deaths occurred (0.7%/year); 83 in the aortic (0.63%/year) and 69 in the mitral/mitro‐aortic (0.81%/year) group. At multivariable Cox proportional hazard regression analysis, female sex was not associated with mortality (HR 0.953, 95%CI 0.678 1.340, P  = .783). Conclusions: Female sex is independently associated with mitral/mitro‐aortic MPHV. Despite a lower TiTR in women, mortality risk did not differ between the two groups.